Factors affecting child marriage and contraceptive use among Rohingya girls in refugee camps - M Mofizul Islam; Md Nuruzzaman Khan; Md Mashiur Rahman (Elsevier, 2021)
Summary: Background: Rohingya girls living in the refugee camps in Bangladesh are disproportionately vulnerable to child marriages and teenage pregnancies. This study examines the factors affecting child marriage and contraceptive use among Rohingya girls who have experienced child marriages.Methods: We collected and analysed quantitative and qualitative data from adolescent Rohingya girls (age 10-19 years) who experienced child marriages. The quantitative data (n=96) came from a cross-sectional survey, and the qualitative data (n=18) from in-depth interviews conducted in the world's largest refugee camp located in Cox's Bazar, Bangladesh. We also interviewed service providers (n=9) of reproductive healthcare services to gain their perspectives regarding contraceptive use among these young girls. We used descriptive statistics to characterise the girls' demographic profiles, ages at their first marriages, and contraceptive use. Thematic analysis was used for the qualitative data to identify key factors influencing child marriage and contraceptive use among these girls.Findings: On average, the adolescent female participants had been 15.7 years old when they were first married. Over 80% had given birth during the two years before the survey or were pregnant during time of the data collection. The main factors that influenced child marriage were found to be perceptions regarding the physical and mental maturity for marriage, social norms, insecurity, family honour, preferences for younger brides and the relaxed enforcement of the minimum legal age for marriage. A third (34%) of the girls said they were using contraceptives on the week when the study was conducted. The desire for children, religious beliefs, misapprehension about contraception and long waiting periods in facility-based health services and current service provision were the main factors influencing contraceptive use. Depo Provera injections and pills were the dominant methods of contraception. Contraceptive use during the period between marriage and the first childbirth is rare.Interpretation: Girl child marriage is common in Rohingya camps. Contraceptive use is rare among newly married girls before they give birth for the first time. The involvement of female and male Rohingya volunteers for outreach services can be catalytic in promoting contraceptive use.Funding: La Trobe Asia, La Trobe University, Melbourne, Australia.Bengali translation of the abstract in Appendix 1